A study of the interaction between inverted cucurbit[6]uril and symmetric viologens. (8th June 2018) - Bai, Dong; Gao, Zhongzheng; Tao, Zhu; Xiao, Xin; Prior, Timothy J.; Wei, Gang; Liu, Qingyun; Redshaw, Carl
Abstract : The interaction between inverted cucuribit[6]uril (iQ[6]) and a series of symmetric viologens bearing aliphatic substituents, namely dicationic dialkyl-4, 4′-bipyridinium guests where the alkyl substituent is CH3 (CH2 ) n ( n = 1, 3 and 5) or benzyl, has been studied in aqueous solution. Abstract : The interaction between inverted cucuribit[6]uril (iQ[6]) and a series of symmetric viologens bearing aliphatic substituents, namely dicationic dialkyl-4, 4′-bipyridinium guests where the alkyl substituent is CH3 (CH2 ) n ( n = 1, 3 and 5) or benzyl, has been studied in aqueous solution by 1 H NMR spectroscopy, electronic absorption spectroscopy, isothermal titration calorimetry and mass spectrometry. The viologen bearing C6 H5 CH2 substituents has also been investigated. In the case of the dialkyl-derived guests, single crystal X-ray diffraction, on crystals grown in the presence of CdCl2, revealed the compositions to be 2(C36 H36 N24 O12 ), 4(C14 H18 N2 ), Cd5 Br9 .56 Cl10 .44 2(H2 O)·2(H3 O); 2(C36 H36 N24 O12 ), C18 H26 N2, 2(CdCl4 ), 36H2 O and 2(C36 H36 N24 O12 ), 2(C11 H17 N), 2(CdCl4 ), 20H2 O for the use of n = 1, 3 or 5 respectively. Thus, in the solid state, in the case of both BV 2+ ( n = 3) and HV 2+ ( n = 5), an interaction of viologen with iQ[6] was observed and the structure adopted is an external 'dumbbell-type' structure.